Review of the rare and little-known Chinese species of the family Taeniopterygidae (Plecoptera), with description of two new species of Kyphopteryx - Du, Yu-Zhou; Chen, Zhi-Teng (Zootaxa, 2019)
The species of the family Taeniopterygidae (Plecoptera) are reviewed from China. Two new Kyphopteryx species, K. yangi sp. nov. and K. coniformis sp. nov. are described and illustrated from Yunnan Province of southwestern China. Additionally, a provisional key to the males of Taeniopterygidae known from China is provided.